Pengaruh Pendekatan Value Clarification Technique (VCT) Metode Percontohan Terhadap Hasil Belajar PKn Siswa Sekolah Dasar - Sakdiah, Halimatun; Reinita, Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This research is motivated by a learning process that is still dominated by teachers in delivering learning and students are not seen active in learning Citizenship Education. This study aims to be able to find out whether there is an influence from the method of the value clarification technique (VCT) on the learning outcomes of students in elementary schools. This research was conducted at SDN Gugus VI District of Akabiluru Regency 50 Kota. This study uses a type of experimental research with Quasi Experiment design. In this study data collection was done by purposive sampling. The sample in this study amounted to 40 people. After the research is done, there is a large t count from t table. Which t count is 1.98 and t table 1.72 with α = 0.05. By getting t count large from t table means Ho is rejected, and Ha is accepted. So it can be concluded that there is an influence of the pilot method of the value clarification technique (vct) on the learning outcomes of students in elementary schools.